Contribution of maternal factors towards birth weight of full-term infants in selected government health clinics in Kuala Lumpur and Selangor, Malaysia - Edi, Muliana (2019)
Birth weight is one of the indicators of suboptimal prenatal growth, which strongly linked to cardio-metabolic condition including central obesity, diabetes mellitus (Type 1 and Type 2), hypertension and heart disease. Foetal adaptation to a poor environment of early life linked with maternal physiological and metabolic changes, which influences the health and illness possibility in later life of infants. Hence, the present study aimed to determine the contribution of maternal factors towards birth weight of full-term infants in selected government health clinics in Kuala Lumpur and Selangor, Malaysia. In overall, 472 pregnant mothers (29.2+4.2 years) participated in this cross-sectional study. They were interviewed for their socio-demographic characteristics, medical history, obstetrical history, emotional state and dietary intake during their third trimester and eventually followed-up until parturition, to acquire birth outcomes when infants at three-month old. Medical record books of the pregnant mothers also were utilised to cross-check the information obtained. A majority of pregnant mothers were Malay (90.9%), attained tertiary educational level (82.0%), working (68.6%), and earned monthly household income within RM2300 to RM5599 (52.8%), and had a mean household size of 3.9+2.0. About half of the pregnant mothers (52.0%) were disease-free before and during pregnancy. Almost half of pregnant mothers were malnourished before pregnancy (Underweight: 9.7%, Overweight: 25.8%, Obesity: 10.9%). There were one in three pregnant mothers gained either insufficient (32.6%) or excessive weight (28.0%) during pregnancy. The present study found more than half of the pregnant mothers experienced multiple pregnancies (65.0%) and had at least one child (57.4%). Almost all of the pregnant mothers (99.2%) were non-smokers, but 40.5% and 26.2% of them were exposed to smoke in their living house and workplace, respectively. Most of the pregnant mothers started their antenatal care visit during first trimester of pregnancy (71.4%), attended an average of 10.8+3.0 times visit and 16.1% of them were at risk of depression during the pregnancy. Most of the pregnant mothers achieved the recommended intakes of nutrients, except for vitamin A, niacin, folate, calcium, and iron. There was about 9.1% of infants being delivered with birth weight of less than 2.5kg, with a mean weight at birth of 3.0+0.4 kg. Based on the multiple logistic regression analysis, pregnant mothers who attained tertiary educational level (OR=2.881), with hypertension during pregnancy (OR=11.814), and energy intake more than recommended nutrient intakes (RNI) (OR=1.022), had higher risk of delivering low birth weight infants, while high gravidity (OR=0.798) and calcium intake more than RNI (OR=0.691) reduced the risk of delivering low birth weight infants, which explained 38.5% of the variances in birth weight of infants (χ²=196.789, p<0.001). Hence, women who plan for pregnancy should make sure they have adequate knowledge before pregnancy, maintain healthy blood pressure and have optimal energy and calcium intake as recommended in RNI during pregnancy to deliver a healthy infant.